A review of polyethylene‐based carbon fiber manufacturing. Issue 3 (9th May 2022) - Röding, Tim; Langer, Jannis; Modenesi Barbosa, Thomaz; Bouhrara, Mohamed; Gries, Thomas
Abstract: Carbon fibers and their composites have attracted much attention in recent years and are being used in an increasing number of industries. However, due to the high production costs of carbon fibers and the complex manufacturing process of composites, their use in large series applications is still limited. The main cost driver in carbon fiber manufacturing is the production of the precursor fiber, with polyacrylonitrile (PAN) being the prevailing feedstock today. Approximately 50% of the production cost of carbon fibers is related to the precursor fiber. For this reason, the use of a new precursor material offers enormous cost‐saving potential. Polyethylene (PE) is a promising alternative to PAN due to its high carbon content, low cost, high availability, and melt processability. This study reviews the research and development activities on PE‐based carbon fibers. The manufacturing of the precursor fiber and its conversion process into a carbon fiber are discussed. The review also provides an overview of published information on concepts for commercial production of PE‐based carbon fibers and various cost models. Abstract : This study reviews the research and development activities on polyethylene (PE)‐based carbon fibers. The manufacturing of the precursor fiber and its conversion process to a carbon fiber are discussed. In the end, the review also gives an overview on the published information about concepts for industrial‐scale production of PE‐based carbon fibers as well as a cost model.